Growing Up in Poverty
XVIII, 284 p.
Keywords: This book presents the latest evidence from Young Lives, a unique international study of children and poverty. It shows how the persistence of inequality amid general economic growth is leaving some extremely poor children behind, despite the promises of the Millennium Development Goals.